Humanization of Care: Key Elements Identified by Patients, Caregivers, and Healthcare Providers. A Systematic Review - Busch, Isolde M.; Moretti, Francesca; Travaini, Giulia; Wu, Albert W.; Rimondini, Michela (The patient : patient-centered outcomes research, 2019)
Given the automatization of care and rationing of time and staff due to economic imperatives, often resulting in dehumanized care, the concept of 'humanization of care' has been increasingly discussed in the scientific literature. However, it is still an indistinct concept, lacking well-defined dimensions and to date no literature review has tried to capture it. The objectives of this systematic review were to identify the key elements of humanization of care by investigating stakeholders' (patients, patients' caregivers, healthcare providers) perspectives and to assess barriers and strategies for its implementation. We carried out a systematic search of five electronic databases up to December 2017 as well as examining additional sources (e.g., gray literature). Search terms included "humanization/humanisation of care" and "dehumanization/dehumanisation of care". We conducted a thematic synthesis of the extracted study findings to identify descriptive themes and produce key elements. Of 1327 records retrieved, 14 full-text articles were included in the review. Three main areas (relational, organizational, structural) and 30 key elements (e.g., relationship bonding, holistic approach, adequate working conditions) emerged. Several barriers to implementation of humanization of care exist in all areas. Our systematic review and synthesis contributes to a deeper understanding of the concept of humanization of care. The proposed key elements are expected to serve as preliminary guidance for healthcare institutions aiming to overcome challenges in various forms and achieve humanized and efficient care. Future studies need to fully examine specific practices of humanized care and test quantitatively their effectiveness by examining psychosocial and health outcomes.